PARTNERSHIP BETWEEN GOVERNMENT AND BUSINESS TO ENSURE THE ECONOMIC SUSTAINABILITY OF COMPLEX INDUSTRIAL OIL AND GAS SYSTEMS IN THE ARCTIC - Sergei S. Yudin; Aleksey E. Cherepovitsyn (Север и рынок: формирование экономического порядка, 2022)
The development of the Arctic’s unique hydrocarbon resources is the basis for Russia’s long-term economic stability and energy security. Hydrocarbon production in the harsh conditions of the Far North is associated with many environmental, technological and organizational difficulties, in this regard, mutually beneficial cooperation between the state and oil and gas market participants in the development of complex industrial oil and gas systems is of particular relevance. Of paramount importance is the development of integration mechanisms to achieve a high level of technological equipment of the Arctic oil and gas complex. The basis for the formation of partnerships is the improvement of the institutional environment for coordinating the multiple interests of the state and business and increasing the economic stability of the Arctic oil and gas systems in the long term. For the purpose of the research, a content analysis of Russian and foreign literature devoted to the processes of combining public and private potential to solve production and management tasks in the mineral resource complex was carried out, the regulatory and legal support for strategic management of the Russian oil and gas sector was analyzed. To study the prospects for the development of strategic partnerships, general scientific methods of analysis, synthesis, decomposition of factors, elements of situational analysis and strategic planning are involved. The article considers the main priorities of Russia’s state policy in the implementation of the oil and gas complex in the Arctic; examines the directions of formation of strategic partnerships between the state and business to ensure the sustainability of industrial oil and gas systems in the face of global challenges; identifies limitations and formulated prospects for the development of the analyzed types of cooperative forms; presents a conceptual scheme of the organization of technological polygons in the Arctic.